Polydatin Ameliorates Osteoporosis via Suppression of the Mitogen-Activated Protein Kinase Signaling Pathway - Lin, Ze; Xiong, Yuan; Hu, Yiqiang; Chen, Lang; Panayi, Adriana C.; Xue, Hang; Zhou, Wu; Yan, Chenchen; Hu, Liangcong; Xie, Xudong; Sun, Yun; Mi, Bobin; et al. (Frontiers in Cell and Developmental Biology, 2021)
Purpose: Polydatin (POL) is a natural active compound found in polygonum multiflorum with reported anti-oxidant and antiviral effects. With the aging population there has been a stark increase in the prevalence of osteoporosis (OP), rendering it an imposing public health issue. The potential effect of POL as a therapy for OP remains unclear. Therefore, we sought to investigate the therapeutic effect of POL in OP and to elucidate the underlying signaling mechanisms in its regulatory process. Methods: The POL-targeted genes interaction network was constructed using the Search Tool for Interacting Chemicals (STITCH) database, and the shared Kyoto Encyclopedia of Genes and Genomes (KEGG). Pathways involved in OP and POL-targeted genes were identified. Quantitative real-time PCR (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) were performed to evaluate the osteogenic genes and the phosphorylation level in pre-osteoblastic cells. In addition, ALP and alizarin red staining was used to test the effect of POL on extracellular matrix mineralization. Results: Twenty-seven KEGG pathways shared between POL-related genes and OP were identified. MAPK signaling was identified as a potential key mechanism. In vitro results highlighted a definitive anti-OP effect of POL. The phosphorylation levels of MAPK signaling, including p38α, ERK1/2, and JNK, were significantly decreased in this regulatory process. Conclusion: Our results suggest that POL has a promising therapeutic effect in OP. MAPK signaling may be the underlying mechanism in this effect, providing a novel sight in discovering new drugs for OP .